The Angular Momentum of Stars Reflects the Relationship between Star-forming Environment and Galactic Evolution History - Yu-Fu Shen; Yan Xu; Yi-Bo Wang; Xiu-Lin Huang; Xing-Xing Hu; Qi Yuan (The Astrophysical Journal)
This study focuses on stars with masses above the Kraft break in the Kepler field. Their rotational angular momenta are essentially the same as those at the zero-age main sequence. The angular momentum dissipation experienced by these stars during their pre-main sequence (PMS) phase is also relatively weak, so their rotational angular momentum can reflect the parameters of their parental molecular clouds. The reliability of angular momentum measurements was evaluated based on the phenomenon of angular momentum conservation observed in stars before and after the turnoff point in observational data. We find that stars with masses between 1.4 M _⊙ and 1.8 M _⊙ show an inverse proportionality between angular momentum and isochrone age. We propose that the angular momentum–age correlation reflects changes in the star-forming environment in the Milky Way’s history. Besides, the observed inverse proportionality implies that as the Milky Way has evolved, the stars formed within it tend to possess greater rotational angular momenta. This trend would promote the fragmentation of stars during the PMS phase and inhibit the formation of massive stars, providing a useful perspective for explaining variations in the initial mass function.